Hubungan Berat Badan Lahir Bayi dengan Kejadian Ruptur Perineum pada Ibu Bersalin di Wilayah Kerja Puskesmas Sei Langkai Kota Batam - Fitri Yunarti; Norma Jeepi; Catur Yulinawati (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Perennial rupture is an injury to the birth canal that occurs during the birth of a baby, whether using tools or not using tools. Perineal rupture is caused by parity, gestational spacing, maternal age, perineal stiffness, birth position. baby's weight, vacuum extraction, instrument trauma, episiotomy and wrong bowel movements. Perineal rupture if not treated immediately will cause bleeding. The aim of this study was to determine the relationship between birth weight of babies and the incidence of perineal rupture in mothers giving birth in the Sei Langkai Community Health Center working area, Batam City in 2023. This research design used cross sectional, the sample taken in this study was 30 people. The processing technique uses the Fisher Exact Test. The data obtained from the results of statistical tests is p-value = 0.037. The conclusion of the research is that the characteristics of the mothers giving birth are mostly aged 20-35 years with most parity being multiparous. Most babies are born with a weight that is not at risk (< 4,000 gr). There is a relationship between the birth weight of the baby and the incidence of perineal rupture in the Sei Health Center Working Area. Langkai with a p-value of 0.037 so that the p-value < α (0.05). It is hoped that this research can be used as input and consideration in further research.